2018
DOI: 10.1371/journal.pone.0207760
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 promotes ectopic periodontal tissue like structure regeneration in LPS-treated PDLSCs

Abstract: Necroptosis is a programmed necrosis, regulated by receptor interacting protein kinase 1(RIP1) and receptor interacting protein kinase 3(RIP3), and could be inhibited by necrostatin-1(Nec-1) specifically. This study aims to evaluate the effect of Nec-1 on LPS-treated periodontal ligament stem cells (PDLSCs). In the research, three groups were established: normal cultured PDLSCs, Porphyromonas gingivalis (Pg)-LPS stimulated PDLSCs and Pg-LPS+Nec-1 treated PDLSCs. The expression of RIP1 and RIP3 and osteogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Cells (1 × 10 5 ) were seeded in six‐well plates and divided into the following six groups: the control group, Pg‐LPS treatment group (LPS), group MI, TAK‐242 treatment group (TAK), MI and Pg‐LPS treatment group (MI + LPS), and MI and Pg‐LPS plus TAK‐242 treatment group (MI + LPS + TAK). The concentration of Pg‐LPS was 10 µg/mL as described by Bingbing Yan 18 . The MI medium contained 10% fetal bovine serum, 50 mg/mL ascorbic acid, 10 mM β‐glycerophosphate, and 100 nM dexamethasone.…”
Section: Methodsmentioning
confidence: 99%
“…Cells (1 × 10 5 ) were seeded in six‐well plates and divided into the following six groups: the control group, Pg‐LPS treatment group (LPS), group MI, TAK‐242 treatment group (TAK), MI and Pg‐LPS treatment group (MI + LPS), and MI and Pg‐LPS plus TAK‐242 treatment group (MI + LPS + TAK). The concentration of Pg‐LPS was 10 µg/mL as described by Bingbing Yan 18 . The MI medium contained 10% fetal bovine serum, 50 mg/mL ascorbic acid, 10 mM β‐glycerophosphate, and 100 nM dexamethasone.…”
Section: Methodsmentioning
confidence: 99%
“…Periodontitis, characterized by tooth mobility and bleeding from gingiva, is a chronic inflammatory disease that causes gingival detachment and disintegration of alveolar bone [1]. It was recently reported that periodontitis broadly affects up to 50% of adults [2]. Previous studies have demonstrated periodontitis is related to systemic conditions such as cardiovascular disease, diabetes mellitus, adverse pregnancy outcomes, and osteoporosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal ligament stem cells are the core examinee stem cells for periodontal regeneration. Due to their self-renewal potential and multidifferentiation capability, PDLSCs have been widely used in tissue regeneration including periodontium [16]. The function and fate of PDLSCs are closely associated with the pathogenesis, progression, treatment, and prognosis in periodontitis [17,18].…”
Section: Discussionmentioning
confidence: 99%